Evolution trend and hot topic measurement of climate migration research under the influence of climate change - Liang, Bing; Shi, Guoqing; Sun, Zhonggen; Babul, Hossain; Zhou, Min (Frontiers in Ecology and Evolution, 2023)
Global climate change, which is characterized by climate warming, has become one of the most prominent risk problems in society at present. Climate migration brings many accompanying problems to the environment, economy, politics, society and culture. It is of great theoretical and practical significance to study the internal relationship between climate change and population migration. The data were extracted from the Web of Science core collection database (WOS) and China Knowledge Network database (CNKI). A total of 785 documents and 157 documents in the field of climate migration from 2008 to 2021 were selected as analysis samples. Word frequency analysis, clustering analysis, sudden word detection analysis, and other methods were extensively used to build the evolution trend map of climate migration using CiteSpace visual bibliometric software. It can be concluded that climate migration research has experienced three stages of development: the initial exploration stage (2008-2011), the development enrichment stage (2012-2017), and the system deepening stage (2018 -). The hot topics of climate migration include: (1) different types of climate migration research; (2) quantitative model research on climate migration; and (3) climate justice research. The study points out that climate migration research is an interdisciplinary field that needs joint research by scholars from different academic backgrounds. In future climate migration research, it is important to: 1) strengthen the prediction ability of the climate change population migration model; 2) make use of China's beneficial exploration in migration fields, such as engineering resettlement, ecological resettlement, and poverty alleviation resettlement, to formulate climate migration policies, regulations, and strategic planning; 3) establish a database cloud platform related to climate change and population migration; and 4) strengthen the exchange and cooperation between Chinese researchers in the field of climate migration and international scientific research institutions.